PERBEDAAN METODE INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE DENGAN DEEP TISSUE MASSAGE DAN CONTRACT-RELAX STRETCHING DALAM MENINGKATAN LINGKUP GERAK SENDI SERVIKAL PADA MYOFASCIAL PAIN SYNDROME OTOT UPPER TRAPEZIUS DI SMA NEGERI 1 SEMARAPURA - I Gede Donny Hendrawan; Nila Wahyuni; I Made Muliarta (Majalah Ilmiah Fisioterapi Indonesia, 2018)
ABSTRACTMyofascial pain syndrome is a collection of sensory, motor, and autonomic symptoms that cause local andreffered pain, limited range of motion and weakness of the affected muscles. The limitations range of motion will beannoying than the daily activities. Interventions that can improve range of motion of cervikal are IntegratedNeuromuscular Inhibition Technique, Deep Tissue Massage and Contract-Relax Stretching. The results show GroupNeuromuscular Inhibition Technique with Wilcoxan Sign Rank Test obtained a mean difference of 13.7 with p = 0.000,while the test results Hypothesis Group Contract-Relax Stretching with Paired Sample T-test showed a mean differenceof 12.1 with p = 0.000. Test the difference between Mann Whitney U-test showed no significant difference between theother group are obtained p = 0.420. These results indicate that there is no difference in increasing range of motion inboth groups.Keywords: Range of motion of cervical, Upper Trapezius Muscle,Myofascial Pain Syndrome, IntegratedNeuromuscular Inhibition Technique, Deep Tissue Massage, Contract-relax Stretching, Goniometer